Arab Pegon dalam Khazanah Manuskrip Islam di Jawa - Jamaluddin Jahuri; Sidik Fauji (Jurnal Penelitian Agama, 2022)
This article attempts to reveal the existence of Arabic pegon and its development in the Islamic manuscript treasures in Java. The script, which was born to accompany the process of islamization in Java, plays an important role in the preservation of Islamic ideas, teachings and traditions in Java, in addition to the hanacaraka script that already existed. By using the paleographic-historical method, this article reveals that Arabic pegon was born from the process of vernacularization of Arabic writing adapted to the Javanese phonological system. Arab pegon was born as an intermediary medium to understand Islamic teachings transmitted in Arabic script, which reached Javanese Muslims who did not have proficiency in Arabic. Not only that, in its development this script was also used for the benefit of the profane Javanese community. Given the wide use of pegon, it is only natural that it became a large part of the Islamic manuscripts in Java from its mere form as a word meaning of a matan at the beginning of its birth, after the XV century, until it became the main text in the XVIII and XIX centuries.